Overlooked lacewings in biological control: The brown lacewing Micromus angulatus and the green lacewing Chrysopa formosa suppress aphid populations in pepper. (22nd April 2022) - Ntalia, Paraskevi; Broufas, George D.; Wäckers, Felix; Pekas, Apostolos; Pappas, Maria L.
Abstract: Lacewings are important natural enemies of soft‐bodied arthropods. Chrysopidae and Hemerobiidae in particular include promising biological control agents of key agricultural pests. Here, we evaluated the efficacy of larvae and adults of the brown lacewing Micromus angulatus and the green lacewing Chrysopa formosa in controlling the green peach aphid Myzus persicae under laboratory conditions. We found that the release of the first instar larvae of both species at the rate of 2 or 10 individuals per pepper plant was effective in reducing the populations of M . persicae, irrespectively of the initial pest infestation pressure, i.e., 10 or 20 aphids per plant. The brown lacewing larvae at the highest release rate managed to completely eliminate the aphids from the pepper plants within two weeks following release. Adult lacewings of both species released at a rate of one to two females per plant were also effective in drastically reducing of M . persicae populations. Our results highlight the potential of these two widespread but overlooked lacewing species for use in biological pest control.